First record of Poemeniinae (Hymenoptera, Ichneumonidae) from Peru, with description of a new species and a key to the world species of Ganodes Townes - Castillo, Carol; Díaz, Francisco A.; Sääksjärvi, Ilari E. (Zootaxa, 2014)
The subfamily Poemeniinae (Hymenoptera, Ichneumonidae) is reported for the first time from Peru. We describe and illustrate a new species, Ganodes atayupanquii sp. n. Castillo & Sääksjärvi, which was collected from the Peruvian Andes at 1500 m. A key to the species of Ganodes Townes and new distribution records of G. wahli Díaz and G. matai Gauld are provided.